Spray-drying microencapsulation of synergistic antioxidant mushroom extracts and their use as functional food ingredients - Ribeiro, Andreia (2015)
In this work, hydroalcoholic extracts of two mushrooms species, Suillus luteus (L.: Fries) (Sl) and Coprinopsis atramentaria (Bull.) (Ca), were studied for their synergistic antioxidant effect and their viability as functional food ingredients tested by incorporation into a food matrix (cottage cheese). In a first step, the individual extracts and a combination of both, showing synergistic effects (Sl:Ca, 1:1), were microencapsulated by spray-drying using maltodextrin as the encapsulating material. The incorporation of free extracts resulted in products with a higher initial antioxidant activity (t0) but declining after 7 days (t7), which was associated with their degradation. However, the cottage cheese enriched with the microencapsulated extracts, that have revealed a lower activity at the initial time, showed an increase at t7. This improvement can be explained by an effective protection provided by the microspheres together with a sustained release. Analyses performed on the studied cottage cheese samples showed the maintenance of the nutritional properties and no colour modifications were noticed.